Studi Deskriptif Tingkat Risiko Terpapar COVID-19 pada Siswa Sekolah Menengah Pertama di Kecamatan Bangkalan Selama Masa Pandemi - Moh Alif Rizkiyanto; Fajar Hidayatullah; Khoirul Anwar (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2021)
The aims to determine the risk level of exposure to COVID-19 in junior high school students in the Bangkalan sub-district after receiving material for the introduction of COVID-19 by the PJOK teacher. During a pandemic like the current PJOK teacher plays an important role in conveying the importance of maintaining cleanliness and health during the pandemic to minimize the risk of being exposed to COVID-19 to their students. This research is a type of quantitative research, this type of quantitative research is research to solve problems that use numbers as data. The population in this study were junior high school students in Bangkalan District, while the sample in this study was 7th grade junior high school students. For the sampling technique using purposive sampling technique, because purposive sampling is a sampling technique or data by determining certain criteria or objectives. The instrument used to measure the level of risk of being exposed to COVID-19 in junior high school students in Bangkalan District is an independent assessment instrument or questionnaire with data taken according to the number of samples in this study. According to the results or data obtained by the researcher, it can be concluded that of the 710 junior high school students who filled out the questionnaire there were no junior high school students in Bangkalan District who were at high risk for exposure to COVID-19 or 0%. then there are 63 junior high school students in Bangkalan sub-district who are at moderate risk for exposure to COVID-19. And 647 Bangkalan District Junior High School students who filled out the questionnaire were at low risk of being exposed to COVID-19.